Perceived Influence of Innovation Management on Library Service Delivery in Selected Academic Libraries in Kwara State, Nigeria - Adeyemi, Ismail; Sanni, Rofiat; Shittu, Ruffiyat; Shiru, Mohammed; Shittu, Faridat (The International information & library review, 2025)
The growing need for innovation management in every component and operations of academic libraries cannot be overemphasized. This study the perceived influence of innovation management on library service delivery in selected academic libraries in Kwara State, Nigeria. The study adopts cross-sectional research design, and questionnaire was adopted for data collection. Out of one hundred and thirty (130) copies of questionnaire administered, only ninety-five (95) were returned completely and valid for the study. The findings indicated that the most adopted innovation management practices include e-learning, innovative human resource management, knowledge management, technology innovation, and leadership competence. The findings showed that the library services provided include circulation/reader services, user education, internet and email services, and research and training services. The findings revealed that innovation management positively influences library service delivery by enhancing knowledge sharing, supporting adaptability, boosting user engagement, fostering staff development, improving access to information, and expanding service delivery. The findings revealed that challenges associated with managing innovation include limited budgets, inadequate staff skills, difficulties in resource management, infrastructure deficiencies, and resistance to change. Results showed that the perceived benefits of innovation management include efficient service delivery, enhanced library image, improved user retention, effective resource use, increased user satisfaction, reduced theft/mutilation, and better organization of resources. The study concludes that with the benefits of innovation management in enhancing efficiency, improved user experiences, and better resource management, libraries still face challenges in implementing innovations. Academic libraries should prioritize fostering an innovation culture and enhancing financial literacy skills among staff.